Identification and Characterization of an Aeromonas hydrophila Oligopeptidase Gene pepF Negatively Related to Biofilm Formation - Du, Hechao; Pang, Maoda; Dong, Yuhao; Wu, Yafeng; Wang, Nannan; Liu, Jin; Awan, Furqan; Lu, Chengping; Liu, Yongjie (Frontiers in Microbiology, 2016)
Bacterial biofilms are involved in adapting to the complex environment and responsible for bacterial persistent infection. The formation of biofilm is a highly complex process during which multifarious genes work together regularly. In this study, we screened the EZ-Tn5 transposon mutant library aiming at identifying the genes involved in biofilm formation of Aeromonas hydrophila. A total of 24 biofilm-associated genes were identified, and the majority of them encoded proteins related to cell structure, transcription and translation, gene regulation, growth and metabolism. The mutant strain TM90, in which a gene encoding oligopeptidase F, pepF, was disturbed, showed significant upregulation of biofilm formation as compared to the parental strain. Meanwhile, the colony phenotype of TM90 became smaller, more transparent and splendent. The adhesive ability of TM90 to HEp-2 cell was significantly increased compared with the parental strain. Fifty percent lethal dose (LD50) determinations in zebraﬁsh demonstrated that the enhanced-bioﬁlm mutant TM90 was highly attenuated relative to the wild-type strain. In conclusion, the pepF gene is first demonstrated to be a negative factor on biofilm formation and involved in pathogenicity of A. hydrophila.